Association between participation in a chronic disease management program, medication adherence and decrease of blood pressure - I Ketut Indra Wiguna Cakera; Ni Made Sri Nopiyani; I Made Ady Wirawan (Public Health and Preventive Medicine Archive, 2018)
Background and purpose: The prevalence of hypertension is increasing globally. A comprehensive approach is necessary including a community based chronic disease management program which has been implemented in public health centres in Indonesia. Only few studies have been published in Indonesia that evaluate the program, especially regarding the management of hypertension in primary care settings. This study aims to examine the association between participation in a chronic disease management program,medication adherence and decrease of blood pressure. Methods: A cross-sectional study was conducted in public health centres in Tabanan District. A total of 136 patients with hypertension were recruited at five groups that participate in the community based chronic disease management program called Program Pengelolaan Penyakit Kronis (Prolanis). The prolanis groups were purposively selected based on the size of participants in the program. One group was selected at urban area and four groups at rural areas. Data were collected from May to June 2017 by conducting interviews, blood pressure measurements, and secondary data extraction from the medical record of the prolanis database. The logistic regression analysis was used to determine the association between participation in a chronic disease management program, medication adherence and decrease of blood pressure. Results: As many as 75.7% of respondents actively participated in the prolanis program, and 81.6% were found with decreased blood pressure. Our study found a significant association between blood pressure decrease and active participation in the prolanis program with an adjusted odds ratio (AOR) of 6.38 (95%CI: 1.96–20.79), the good adherence towards medication with AOR=11.94 (95%CI: 3.60–39.56), and routine physical activities with AOR=3.84 (95%CI: 1.16-12.73). Conclusion: Active participation in the prolanis program, good adherence to medication and routine physical activities are independent factors of decreased blood pressure. These findings suggest the need for scaling up the prolanis program and increasing its coverage.